Pengembangan Instrumen Kemampuan Berpikir Kritis dan Kreatif dalam Konteks Socioscientific Issues pada Materi Sumber Energi untuk Siswa SMA - Nurul Diah Azhari; Yuberti; Irwandani (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2026)
The changing orientation of physics assessment requires instruments that measure not only conceptual mastery but also students’ ability to evaluate evidence, construct arguments, and formulate solutions to socio-scientific problems. This study aimed to develop and evaluate the feasibility of an instrument for assessing critical and creative thinking skills in the context of socioscientific issues (SSI) on energy sources for senior high school students. The study employed the 4D development model, limited to the define, design, and develop stages. The research subjects consisted of three expert validators, one physics teacher, and 34 Grade X science students at MA Guppi Banjit Way Kanan as users in a limited trial. The product consisted of 12 contextual essay items integrating issues of energy sources, fossil energy limitations, renewable energy, and socio-environmental impacts. Data were collected using validation sheets for assessment experts, material experts, and language experts, teacher response questionnaires, student response questionnaires, and readability testing. The validation results showed that the instrument was in the highly feasible category, with an average score of 91.67% from the assessment expert, 89.58% from the material expert, and 90.63% from the language expert. The teacher response reached 92.50%, while the student response reached 88.72%, both categorized as highly feasible. These findings imply that the SSI-based instrument can be used by teachers as a diagnostic and formative assessment tool to map the quality of students’ argumentation, evidence evaluation, and creative solutions in learning about energy sources.